Advancements in visible light responsive MOF composites for photocatalytic decontamination of textile wastewater: A review. (May 2022) - Mukherjee, Debarati; Van der Bruggen, Bart; Mandal, Bishnupada
Abstract: Heterogeneous photocatalysis using metal-organic frameworks (MOFs) is expected to provide a pivotal solution for the remediation of toxic dyes and heavy metals from textile wastewater. However, MOFs often suffer from a low removal efficiency, due to the rapid recombination between holes and electrons, generated upon photoexcitation. Additionally, the MOFs exhibit poor water stability, which restricts their large-scale application. In this regard, various approaches (i.e. doping of metal nanoparticle, semiconductor, quantum dot, and ligand functionalization) have been adopted for the formation of multifunctional composites. The MOF-composites possess suitable photochemical, surface, optical, and electronic properties, resulting in enhanced water stability, visible light absorption, and reduced recombination between photogenerated species. This comprehensive review targets to provide an insight into the synthesis and subsequent application of various MOF composites for photocatalytic removal of organic contaminants (dyes) and inorganic (Cr(VI)) contaminants from water. MOFs/graphene oxide composites possess improved surface area and reusability whereas noble metal incorporated MOFs composites suffer from photocorrosion and are relatively costly. Zr and Ti based MOFs exhibit tuning from UV to visible light response and surpass the poor water stability upon binary/ternary composite formation. The role of the dopants in enhancing the efficiency of the composites; the effect of influencing factors such as solution pH, pollutant concentration; the mechanism, and the kinetics of reactions have been outlined. In spite of many advancements, the article also summarizes some roadblocks that need to be unraveled to achieve the energy-water-environment nexus and scope for future breakthrough research in this field. Graphical abstract: Image 1 Highlights: Toxic dyes and heavy metals in textile wastewater adversely affect the ecosystem. Photocatalyst should be visible light responsive, have reduced e − - h + recombination. Formation of heterojunction, Schottky junction, SPR improves charge separation. Core-shell structures of composites exhibit enhanced water stability. Photocatalytic degradation follow pseudo first order reaction kinetics.